Risk of adverse outcomes following urinary tract infection in older people with renal impairment: Retrospective cohort study using linked health record data. - Haroon Ahmed; Daniel Farewell; Nick A Francis; Shantini Paranjothy; Christopher C Butler (PLoS Medicine)
Background Few studies have investigated the risk of adverse outcomes in older people with renal impairment presenting to primary care with a urinary tract infection (UTI). The aim of this study was to determine the risk of adverse outcomes in patients aged ≥65 years presenting to primary care with a UTI, by estimated glomerular filtration rate (eGFR) and empirical prescription of nitrofurantoin versus trimethoprim. Methods and findings This was a retrospective cohort study using linked health record data from 795,484 patients from 393 general practices in England, who were aged ≥65 years between 2010 and 2016. Patients were entered into the cohort if they presented with a UTI and had a creatinine measurement in the 24 months prior to presentation. We calculated an eGFR to estimate risk of adverse outcomes by renal function, and propensity-score matched patients with eGFRs <60 mL/minute/1.73 m2 to estimate risk of adverse outcomes between those prescribed trimethoprim and nitrofurantoin. Outcomes were 14-day risk of reconsultation for urinary symptoms and same-day antibiotic prescription (proxy for treatment nonresponse), hospitalisation for UTI, sepsis, or acute kidney injury (AKI), and 28-day risk of death. Of 123,607 eligible patients with a UTI, we calculated an eGFR for 116,945 (95%). Median age was 76 (IQR, 70-83) years and 32,428 (28%) were male. Compared to an eGFR of >60 mL/minute/1.73 m2, patients with an eGFR of <60 mL/minute/1.73 m2 had greater odds of hospitalisation for UTI (adjusted odds ratios [ORs] ranged from 1.14 [95% confidence interval (CI) 1.01-1.28, p = 0.028], for eGFRs of 45-59, to 1.68 [95% CI 1.01-2.82, p < 0.001] for eGFRs <15) and AKI (adjusted ORs ranged from 1.57 [95% CI 1.29-1.91, p < 0.001], for eGFRs of 45-59, to 4.53 [95% CI 2.52-8.17, p < 0.001] for eGFRs <15). Compared to an eGFR of >60 mL/minute/1.73 m2, patients with an eGFR <45 had significantly greater odds of hospitalisation for sepsis, and those with an eGFR <30 had significantly greater odds of death. Compared to trimethoprim, nitrofurantoin prescribing was associated with lower odds of hospitalisation for AKI (ORs ranged from 0.62 [95% CI 0.40-0.94, p = 0.025], for eGFRs of 45-59, to 0.45 [95% CI 0.25-0.81, p = 0.008] for eGFRs <30). Nitrofurantoin was not associated with greater odds of any adverse outcome. Our study lacked data on urine microbiology and antibiotic-related adverse events. Despite our design, residual confounding may still have affected some of our findings. Conclusions Older patients with renal impairment presenting to primary care with a UTI had an increased risk of UTI-related hospitalisation and death, suggesting a need for interventions that reduce the risk of these adverse outcomes. Nitrofurantoin prescribing was not associated with an increased risk of adverse outcomes in patients with an eGFR <60 mL/minute/1.73 m2 and could be used more widely in this population.